A RAPID REVIEW ON ROBOTIC (EXOSKELETON) TO EVALUATE BALANCED, STANDING AND WALKING (Journal of Pharmaceutical Negative Results, 2022)
Balance evaluation during standing and walking is efficient chiefly in people with neural compensations. Rehabilitation robots, on the other hand, might make evaluation processes easier and increase their clinical usefulness. We analysed the possible use of robotic instruments for such assessments based on this overview. The uniqueness and presumed key benefits of utilising robots for assessment include their capacity to assess severely afflicted patients by offering assistance-when-needed, as well as their ability to give constant perturbations while standing and walking while recording the patient's reactions. We classify robotic devices based on three factors that are significant to their potential application in balance assessment: 1) the device's interaction with the human body; 2) on what surface the individual stands or walks when using the gadget, and 3) To what extent the wearable devices are. Also, robotic support was easy to use with no undesirable effects of skin abrasions or soreness.